Living Qur'an: The Study of Qolbul Qur`an Reading Practice at Majlis Mistiqbigh in Seduri, Wonodadi, Blitar - Abdur Rohman, Ali; Haidar Ali, Afan (IAIN Madura, 2024)
This article examines the tradition of Qolbul Al-Qur'an recitation at Majlis Mistiqbigh in Seduri, Wonodadi, Blitar, regularly practiced as an act of worship to strengthen the congregation’s connection to Allah SWT and as an expression of religious identity. Academically, it addresses the need for in-depth study on the preservation and transmission of Quran-based traditions as living cultural practices. The study aims to understand the meanings embedded in Qolbul Al-Qur'an recitation and its spiritual impact on the community. Using the Living Quran approach and Karl Mannheim's theory, the study explores three dimensions of meaning: objective, expressive, and documentary. The findings reveal that the objective meaning of this tradition is to foster the spiritual growth of the Seduri, Wonodadi, and Blitar communities, nurturing a deep reverence for the Qur'an. The expressive dimension reflects the congregation’s belief in the blessings and virtues of Qur'anic recitation, while the documentary meaning underscores the tradition’s roots and continuity in the community. In conclusion, the Qolbul Al-Qur'an recitation is not only a spiritual practice but also a foundational element shaping the religious and cultural identity of the local society, ensuring the community’s enduring connection to the Qur'an.